Peran Pembiayaan Produktif BMT Mandiri Mulia Terhadap Peningkatan Kesejahteraan Anggota Perspektif Maqasih Syariah - Muhammad Hidayatulloh; Meri Indri Hapsari (Universitas Airlangga, 2015)
The purpose of this study is to understand and analyze the role of BMT Mandiri Sejahtera Financing Productive for members welfare improvement. Method used in this study was descriptive qualitative approach with the case-study research. This research had analysis unit which were BMT Mandiri Sejahtera Financing Productive and welfare improvement of the members that received the financing activities.The result of this study was that the BMT Mandiri Sejahtera Financing Productive took role in improving the walfare of the members. Welfare was measured by using the 5 indicators of basic needs maintanance, based on maqashid syariah, which are the religion maintanance, life maintenance, upkeep sense, descendants maintenance, and property maintenance. The improvement of welfare experienced by the members were different. Generally, the walfare improvement of the members who received BMT Mandiri Sejahtera only happenedin several basic needs maintanance.